The relationship between carbon emissions intensity and sustainable growth rate: The moderating role of media exposure - Amrullah, Muhamad Tohir; Sari, Martdian Ratna (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study investigates the relationship between carbon emissions intensity (CEI) and sustainable growth rate (SGR), with media exposure as a moderating variable. Using data from energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024, the research applies quantitative methods with moderated regression analysis (MRA). The results reveal that CEI has no significant effect on SGR, and media exposure does not significantly moderate this relationship. These findings suggest that despite maintaining of carbon emissions, public and media pressure on environmental issues in Indonesia remains weak and insufficient to influence corporate sustainable growth strategies. The study contributes to the literature by providing empirical evidence from an emerging market context and by introducing media exposure, measured through a modified Janis–Fadner coefficient, as a novel moderating variable in environmental accounting research. The results highlight the limited role of media as a social control mechanism in Indonesia and underscore the need for stronger regulatory intervention and stakeholder engagement to promote sustainability in high-emission industries.